2018
DOI: 10.22323/2.17020207
|View full text |Cite
|
Sign up to set email alerts
|

An inconvenient source? Attributes of science documentaries and their effects on information-related behavioral intentions

Abstract: We investigate the impact of a science documentary on individuals' intention to engage in information-related behaviors by experimentally testing the effects of source type (scientist, politician, or anonymous source) and communication setting (interview or lecture) using a manipulated clip from the documentary, ‘An Inconvenient Truth’. Our results indicate that, compared to anonymous sources, use of authoritative ones result in greater intention to engage in some information-related behaviors. Additionally, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Previous research discovered that user-generated science videos were more popular than professionally produced videos on YouTube and that having consistent science communicators deliver the content might increase video popularity [ 21 ]. Use of authoritative spokespersons (e.g., politicians, scientists) rather than anonymous narrators in presenting controversial scientific topics in documentary films appeared to increase viewer engagement with the content [ 62 ]. In addition, experimental evidence showed that viewers reported greater interest and perceived relevance concerning chemistry when viewing chemistry content that focused on applications of science in people’s everyday life [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research discovered that user-generated science videos were more popular than professionally produced videos on YouTube and that having consistent science communicators deliver the content might increase video popularity [ 21 ]. Use of authoritative spokespersons (e.g., politicians, scientists) rather than anonymous narrators in presenting controversial scientific topics in documentary films appeared to increase viewer engagement with the content [ 62 ]. In addition, experimental evidence showed that viewers reported greater interest and perceived relevance concerning chemistry when viewing chemistry content that focused on applications of science in people’s everyday life [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this is that participants might have assessed politicians and researchers to be more influential actors compared to the citizens' jury, as for both groups in both statement conditions the correlation between source credibility and acceptance was significantly positive. Recent research supports this finding, as Yeo, Binder, Dahlstrom and Brossard [2018] found, that authoritative sources like politicians or researchers had a significant impact on behavioural intentions, whereas an anonymous source had not. Though the citizens' jury was perceived as trustworthy, respondents did not adjust their acceptance rating based on its statement.…”
Section: Discussionmentioning
confidence: 77%
“…The results of our experiment suggest that for the communication of science in online videos, the traditional expository style of narration still carries advantages. It is generally perceived as more authoritative and, therefore, believable (Yeo et al, 2018). This is probably a consequence of our exposure to the style of traditional science documentaries (León, 2007).…”
Section: Discussionmentioning
confidence: 99%